The Decline of Significance in Today’s Digital Media Formats - STERIAN, Alexandru (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
Does modern digital media reconfigure the film’s message? The ubiquity of interactive screens alters the social and emotional human interactions. Through the advent of digital media within the film workflow, the ontological referentiality of the analog support becomes obsolete. The medium digital support can influence the meaning and structure of the message, which gradually starts losing its primary meanings due to the shallow, inattentive film viewing. Starting with the aesthetic approaches and visual codes, the movie’s distribution begins to replace some disputable values which the film as an art has preserved within its DNA, emotion and empathy. How much of the iconic stage of a sign is still embedded within a support without an ontic representativity, expressed today through mathematic algorithms and digital codes?